Effect of the Extracellular Vesicle RNA Cargo From Uropathogenic Escherichia coli on Bladder Cells - Dauros-Singorenko, Priscila; Hong, Jiwon; Swift, Simon; Phillips, Anthony; Blenkiron, Cherie (Frontiers in Molecular Biosciences, 2020)
Iron restriction in mammals, part of innate antimicrobial defence, may be sensed as a signal by an infecting pathogen. Iron-dependent regulators not only activate the pathogen’s specific iron acquisition and storage mechanisms needed for survival but also influence a number of other processes. Bacterial Extracellular Vesicles (EVs) are a conserved communication mechanism, which can have roles in host colonisation, transfer of antimicrobial resistance, modulation of the host’s immune response and biofilm formation. Here we analyse the iron-responsive effect of RNA cargo from Escherichia coli EVs in bladder cells. No differences were found in total RNA quantified from EVs released from representative pathogenic and probiotic strains grown in different iron conditions, nevertheless, lipopolysaccharide (LPS) associated with purified RNA was 10 times greater from EVs derived from the pathogenic strain. The pathogen and probiotic EV-RNA have no substantial toxic effect on the viability of cultured bladder cells, regardless of the iron concentration during bacterial culture. Transcriptomic analysis of bladder cells treated with pathogen EV-RNA delivered in artificial liposomes revealed a gene expression profile with a strong similarity to that of cells treated with liposomes containing LPS alone, with the majority being immune response pathways. EV-RNA from the probiotic strain gave no significant perturbation of gene expression in bladder cells. Cytokine profiling showed that EV-LPS has a role modulating the immune response when internalised by bladder cells, highlighting a key factor that must be considered when evaluating functional studies of bacterial RNA.